Cymbopleura huohuaensis sp. nov. (Cymbellaceae; Bacillariophyceae), a new species from Sichuan Province, China - Guo, Ji-Shu; Meng, Wen-Wen; Kociolek, John Patrick; Yang, Sophia; Li, Yan-Ling (Phytotaxa, 2022)
Cymbopleura huohuaensis sp. nov. is identified as a new species and described from stone surfaces in Huohua Lake, Sichuan Province, China. A detailed morphological description of the new species is presented, based on light and scanning electron microscopy. Cymbopleura huohuaensis sp. nov. has the features that assign it to the genus Cymbopleura, including the raphe with dorsally deflected terminal fissures and ventrally curved central raphe ends, punctate-lineate striae, and the absence of apical pore fields and stigmata. There are five features that easily distinguish the new species from the other similar taxa within the genus: 1) linear-lanceolate central area, 2) mostly slit-like, partly T-shaped, V-shaped or irregularly-shaped areolae, 3) strongly reverse-lateral raphe, 4) slightly truncate to obtusely rounded ends and 5) the highest density of areolae (30–50 in 10 μm). Among the currently described species of Cymbopleura, the new species is in general most similar to C. subaequalis var. pertruncata in valve shape and possessing a reverse-lateral raphe, but is easily distinguished from that taxon by the size and shape of valve, shape of central area, and the degree of asymmetry about the apical axis and its notable lack of an intermissio. This species might be better placed in the C. austriaca group due to its lack of an intermissio. These findings increase our understanding the morphology and distribution of the genus Cymbopleura in China.